Sustainability and innovation: a blended approach to peer mentor leader training - Jason John Hettrick (Association for Learning Development in Higher Education (ALDinHE), 2015)
Peer Assisted Study Sessions (PASS) is an established part of widening participation and retention activities at the University of Cumbria. In October 2013, the question of sustainability and growth of the scheme was addressed. The small team of PASS supervisors needed to create an effective and innovative way to meet the challenges of growing and maintaining the universityÃ¢â¬â¢s most successful peer mentoring scheme. To this end a new blended approach to PASS training was trialled in 2014. The training combined a range of face-to-face support, training and debriefs (plus online elements), via a virtual learning environment (VLE) and Facebook. Having been successful in both implementation and outcomes, this new blended approach to delivering training has now been adopted by the PASS supervisor team.